1998
DOI: 10.1136/bmj.317.7168.1275
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of effects of early discharge after surgery for breast cancer

Abstract: Objective To determine the effect of early discharge from hospital after surgery for breast cancer on physical and psychological illness. Design Randomised controlled trial comparing discharge two days after surgery (before removal of drain) with standard management (discharge after removal of drain). Setting Regional breast unit. Subjects 100 women with early breast cancer undergoing mastectomy and axillary node clearance (20) or breast conservation surgery (80). Main outcome measures Physical illness (infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
64
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 8 publications
3
64
1
5
Order By: Relevance
“…Although it is possible to discharge patients early without a wound drain in situ (Purushotham et al, 2002), this has not become standard practice. This trial provides further evidence that early discharge for patients recovering from axillary clearance for breast cancer is safe (Bonnema et al, 1998a;Bundred et al, 1998;Horgan et al, 2000). In addition, this study provides novel data on patients, the applicability of early discharge to an unselected population of patients with breast cancer, and the benefits and burdens of early discharge or conventional stay for carers and primary or secondary health care services.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Although it is possible to discharge patients early without a wound drain in situ (Purushotham et al, 2002), this has not become standard practice. This trial provides further evidence that early discharge for patients recovering from axillary clearance for breast cancer is safe (Bonnema et al, 1998a;Bundred et al, 1998;Horgan et al, 2000). In addition, this study provides novel data on patients, the applicability of early discharge to an unselected population of patients with breast cancer, and the benefits and burdens of early discharge or conventional stay for carers and primary or secondary health care services.…”
Section: Discussionmentioning
confidence: 81%
“…Randomised controlled trials carried out in Holland (Bonnema et al, 1998a) and England (Bundred et al, 1998;Horgan et al, 2000) have suggested that early discharge following axillary clearance has no adverse effect on physical or psychological outcome, and is acceptable to patients. There are indications that early discharge (with drains in situ) may enhance shoulder movement (Bundred et al, 1998), reduce wound pain (Bundred et al, 1998) and improve family support (Bonnema et al, 1998a), and it has been assumed that financial benefits to the Health Service will ensue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies indicating that well-informed patients who received good quality care are satisfied even when MLOS is cut radically (13,14) This would suggest that well-managed rationalization is not in opposition to the patient's needs and interests.…”
Section: Discussionmentioning
confidence: 99%
“…Bundredet al (22) found no negative effect of early discharge on physical and psychological illness and advised early discharge for patients who were provided with informal care at home. In addition,the advantages of a short LOS includes less workload on staff, savings on hospital charges, reduction in waiting lists, and shift from expensive hospital care to cheaper home care (23).…”
Section: Discussionmentioning
confidence: 99%